Examining the Use of Corporate Governance Mechanisms in Public–Private Partnerships: Why Do They Not Deliver Public Accountability?. Issue 3 (September 2017) - Stafford, Anne; Stapleton, Pamela
Abstract: The paper examines corporate governance mechanisms which aim to ensure financial accountability in the context of long‐term Public–Private Partnership (PPP) contracts in Britain, and assesses the degree to which they provide taxpayers with control and accountability. The corporate governance arrangements are drawn from the private sector, and therefore downplay the traditional concepts of probity and stewardship, in part due to the British Treasury's adoption of private sector financial reporting. The paper draws on Shaoul et al.'s (2012a) governance‐based reporting framework to critique the corporate governance mechanisms of structure, financial reporting, contracts, and scrutiny in relation to British PPP projects. It shows that the way these mechanisms are set up means there is a lack of control by the public sector, thus rendering public accountability ineffective. Abstract : PPP corporate governance arrangements are drawn from the private sector and therefore downplay traditional concepts of probity and stewardship as they have only limited requirements for reporting, public governance, oversight and accountability and moreover lack transparency. The deficiency of public control renders the mechanisms ineffective.